THE INFLUENCE OF THE NUMBERS OF RESIDENTS TO THE FUNCTION AND CONVENIENCE OF MOTION ON RUSUNAWA, WEST JATINEGARA, JAKARTA’S RESIDENTIAL UNITS - Permatasari (Jurnal Riset Arsitektur, 2018)
Abstract- The relocation of dwellers who resided in riverbanks to flats has been implemented as part of Ciliwung river normalization project to reduce the occurrence of floods in Jakarta. In 2015, the Local Government of Capital City Jakarta had been relocated residents of Kampung Pulo to Jatinegara Rental Flats. But in fact, there were differences of population number and lifestyles between the occupants during the building design process and the occupants who were actually being relocated so there were discrepancies betwen the two communities’ characteristics. Therefore, the number of occupants living in the residential flat units typically exceeds the ideal capacity that should be accommodated and can influence the function and comfort of motion of flats’ residential units.This study used qualitative descriptive method by mapping and grouping the space functions and placement of furnitures in the flats units, also comparing the placement of furnitures to human anthropometry standards, as well as researching the activities and perceptions of the occupants in the Jatinegara Barat Rental Flats units.The aim of this study was to answer the research questions by analyzing the influence of the number of occupants to the functionality and comfort of motion at Jatinegara Rental Flats’ residential units. This research is conducted hopefully to provide suggestions for improvements of flats design that are intended for dwellers who occupies the river banks area and are being relocated in order to make a better dwelling space in Jakarta to fulfill the functionality and comfort of motion at vertical housings.The functionality and comfort of motion at the West Janitnegara Rental Flats units beside influenced by the number of occupants living in residential units, are also causes by activities of residents who are living in residential units within a certain time unit, the limited area of residential units, the placement and quantity of furnitures owned by the residents, and some restrictions about ownership and management of rental flats units. Key Words: number of occupants, residential function, comfort in motion, West Jatinegara Rental Flats.